Meningkatkan Percaya Diri Anak Kelompok B melalui Metode Gerak dan Lagu di PAUD KB Gong Lestari Otak Kebon - Maududi, Ahmad (YASIN, 2022)
Confidence is a feeling that always believes in one's own abilities, does not depend on others, can socialize well under any conditions, has good self-control, respects one another and is able to deal with various problems, is productive, likes new things and likes to face challenges. For this reason, it is very important to develop children's self-confidence from an early age, one of the ways that can be done to increase children's self-confidence is the method of movement and songs. This research is a Classroom Action Research (CAR), which consists of two cycles, with each cycle consisting of planning, action, observation and reflection. Sources of data came from teachers and kindergarten students Group B gong lestari otak kebon. Data collection techniques in this study used three procedures, namely observation, performance and documentation. The data analysis technique used is a qualitative analysis technique in the form of observations on the learning process and analysis of quantitative data in the form of scores resulting from the performance observation sheets carried out at the end of each learning cycle using the motion and song method. Based on the results of the research that has been carried out, it can be concluded that through the method of movement and song can increase the confidence of group B children in PAUD KB Gong Lestari Otak Kebon for the 2021/2022 academic year.